PELATIHAN KURIKULUM DAN PENDAMPINGAN PEMBUATAN APE BAGI GURU PAUD DI KOTA SEBULU DAN KECAMATAN MUARA KAMAN KABUPATEN KUTAI KARTANEGARA - Norlaila; Sri Purwanti; Vitriana, Bety (Politeknik Negeri Sriwijaya, 2023)
Through curriculum training and assistance in making APE or educational learning tools, it is hoped that PAUD teachers can improve their ability to implement the learning process in a more targeted, innovative, creative and effective way. In addition, it is hoped that PAUD teachers can gain new knowledge and information that will help them provide quality and high-quality education for the nation's next generation at the most basic formal education level in Kutai Kartanegara. This training was aimed at PAUD teachers in Kutai Kartanegara, and was held in the SPS AL-Qur'an Hall. This service method is carried out through two days of training. On the first day, material was delivered and on the second day, microteaching practice was carried out. It can be seen that the implementation of this service optimizes PAUD teaching staff and provides skills to PAUD teachers in compiling learning curricula and making educational learning tools while improving the quality of human resources at the PAUD unit level.